Structural Determinants of the APOBEC3G N-Terminal Domain for HIV-1 RNA Association - Fukuda, Hirofumi; Li, Songling; Sardo, Luca; Smith, Jessica L.; Yamashita, Kazuo; Sarca, Anamaria D.; Shirakawa, Kotaro; Standley, Daron M.; Takaori-Kondo, Akifumi; Izumi, Taisuke (Frontiers in Cellular and Infection Microbiology, 2019)
APOBEC3G (A3G) is a cellular protein that inhibits HIV-1 infection through virion incorporation. The interaction of the A3G N-terminal domain (NTD) with RNA is essential for A3G incorporation in the HIV-1 virion. The interaction between A3G-NTD and RNA is not completely understood. The A3G-NTD is also recognized by HIV-1 Viral infectivity factor (Vif) and A3G-Vif binding leads to A3G degradation. Therefore, the A3G-Vif interaction represents a novel target for the development of antiviral therapies that block HIV replication. However, targeting the A3G-Vif interactions could disrupt the A3G-RNA interactions that are required for A3G’s antiviral activity. To better understand A3G-RNA binding, we generated in silico docking models to simulate the RNA-binding propensity of A3G-NTD. We simulated the A3G-NTD residues with high RNA-binding propensity, experimentally validated our prediction by testing A3G-NTD mutations, and identified structural determinants of the A3G-RNA binding. The new structural insights provided here will facilitate the design of pharmaceuticals that inhibit A3G-Vif interactions without negatively impacting A3G-RNA interactions.